Can Co-enzyme Q10 improve the chances of conception after the age of 35? - Abd El Fattah, Eman Ali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: ovarian follicular quality diminishes with age, Free radicals and oxidative stress begin to accumulate in cells, aging or slowing down the metabolic energy production centers in the cell- the mitochondria. When the mitochondria cannot generate a certain amount of energy, it slows growth and proper development of the follicle making it more prone to DNA damage, including chromosomal abnormalities resulting in poor fertilization patterns, and early miscarriage. Co-enzyme Q10 (CoQ10) is a major cellular antioxidant. its tissue levels gradually decrease with age. We attempt to evaluate its protective effect on ROS-induced ovarian damage, which is one of the most important and widely accepted patho- mechanisms underlying cell ageing. Methods: 40 Participants from El Shatby hospital infertility clinic 35 to 38 years old, with history of bad response to ovulation stimulation, were divided into two equal groups (group A given (CoQ10) 3mg|kg body weight for three cycles prior to stimulation Serum anti- mullarian hormone level was measured before and after CoQ10 administration, group B= twenty cases as control). Participants were given gonadotrophins (150 IU to 375 IU). Follicular growth was monitored by trans- vaginal ultra- sonography and serum estradiol level (E2). Ovulation trigger was achieved using 10,000 IU of human chorionic gonadotrophin. Results: The primary outcome was occurrence of normal pregnancy; secondary outcome was good response to stimulation (at least one mature follicle 18-22mm). Conclusions: CoQ10 has no significant effect on response to ovulation stimulation or on pregnancy rates.